Effects of Catalysts, Solvents, and Temperature on Nenitzescu Reaction - Zunzunwala, Kajal; Kumari, Shreya; Gaur, Yash Kumar; Pathak, Dharam Pal; Das Gupta, Ghanshyam; Sharma, Kalicharan (Current Organic Chemistry, 2026)
Indole derivatives possess a wide range of biological activities, including antibacterial, anti-inflammatory, analgesic, and anticancer properties. The Nenitzescu reaction is a valuable approach for their synthesis; however, there are challenges, such as the limited availability of dinitro derivatives and complex workup procedures, which necessitate optimization and improvement in practical efficiency. The Nenitzescu reaction is a versatile method for synthesizing hydroxyindoles, particularly 5-hydroxyindoles. 5-Hydroxyindoles play a crucial role as fundamental components in a wide range of natural chemicals and pharmaceuticals. This reaction has the potential to be applied in the fields of medicinal chemistry and natural product synthesis. The selection of catalysts, solvents, and temperature is a crucial factor in maximizing yields. Scientists have examined different solvents, catalysts, and reaction conditions in order to improve the output and effectiveness of the Nenitzescu process. The objective of this study is to examine the requirements for producing 5-hydroxyindoles by the Nenitzescu reaction. The study investigates the influence of catalysts, solvents, and reaction temperatures on the yield of the reaction. The main emphasis is on the Nenitzescu reaction, with the objective of enhancing its practicality and environmental friendliness. Several trials using various solvents and catalysts are conducted. Nitromethane and acetic acid serve as effective solvents. The cyclization of hydroxy indoles is enhanced by zinc halides, specifically ZnCl2 or ZnI2.
Keywords: benzoquinone